Rural Road Development in India : An Assessment of Distribution of PMGSY Project Benefits in Three States by Gender and Ascribed Social Groups - World Bank (Washington, DC, 2014)
In 2000, the Government of India launched the Pradhan Mantri Gram Sadak Yojana (hereinafter PMGSY) with the primary objective of providing all-weather road connectivity (with necessary culverts and cross-drainage structures operable throughout the year), to eligible unconnected habitations in rural areas. Currently, about 60 percent of the 170,000 eligible habitations have a road. By the end of 2010, expenditures for the program had amounted to about US$14.6 billion, and a further US$40 billion is estimated to be required to complete the program by 2020 (World Bank, 2010). The PMGSY program is a very large undertaking with the World Bank also being involved in its financing and execution all along; the most recent credit amounted to US$1.4 billion. This report summarizes findings based on data collected as part of the primary survey, coupled with findings from the qualitative survey which included focus group discussions (FGDs). It highlights findings which answer the six key questions which are relevant to decision makers as evidence to improve existing and proposed programs and for further policy dialogue. This is a short version of a separate detailed report which in addition to the key findings of the quantitative and qualitative surveys has annexes on key impacts and detailed findings by state. The detailed analysis and tables generated are part of the full statistical analysis report by international consultants and the preliminary findings report which will serve as background reports for reference as required. It is hoped that the report(s) will make a useful contribution to the process of drawing up recommendations to improve PMGSY's impact in the sphere of ascriptive distribution - in short, on its 'inclusiveness'.